UJI KLINIK PENGGUNAAN BACTESYN DIBANDING LINCOMYCIN PADA PENDERITA YANG DILAKUKAN ODONTEKTOMI DI RUMAH SAKIT ATMA JAYA - FX. Srie Rahayu Kustini (Journal of Dentistry Indonesia, 2015)
Bactecyn is an antibiotic that contains sultamicillin. This antibiotic is a complex of combination between ampicillin and sulbactam is double ester bond. Whis makes Bactesyn become an antibiotic with broader spectrum. Lincomycin is an antibiotic, which is ideal enough to treat dentoalveolar infections. This antibiotic is well known among the fellow dentist in Atma Jaya Hospital. It is obvious that these two medicines are very effective to deal with infections arising after operations of impacted teeth. The dose of Bactesyn is 375 mg, given twice a day, whereas, Lincomycin is 500 mg, given three times daily.